NOTE ON THE SYSTEMATICS AND BIONOMICS OF CHANDA SPP. (CENTROPOMIDAE) - Gupta, S K (Indian Journal of Fisheries, 2011)
Enlargement in the ranges of variations in morphometric features of Clianda noma (Ham.) and Chanda ranga (Ham.) from Banda (U.P.) is recorded and compared with the earlier descriptions. In the present study ’noma’ is retained under genus Chanda instead of HamUtonia, as proposed by Brunner (1954), on the basis of differences noticed in the key characters. Bionomical notes on the two species are also added.